Malaysia's foreign policy : the first fifty years : alignment, neutralism, Islamism - 233197 Saravanamuttu, J. (Jayaratnam); Institute of Southeast Asian Studies (Singapore : Institute of Southeast Asian Studies, 2010)
Includes bibliographical references (p. 351-367) and index